Emotional and autonomic response to visual erotic stimulation in patients with functional hypothalamic amenorrhea - Maiorana, Natale; Brugnera, Agostino; Galiano, Valentina; Ferrara, Rosanna; Poletti, Barbara; Marconi, Anna Maria; Garzia, Emanuele; Ticozzi, Nicola; Silani, Vincenzo; Priori, Alberto; Ferrucci, Roberta (Frontiers in Endocrinology, 2022)
Functional hypothalamic amenorrhea (FHA) is a clinical condition associated with high levels of physiological and psychological stress ranging from weight loss to maladaptive behavior and coping skills. A reliable measure of the psychophysiological response to stress and the ability to cope with stimuli is heart rate variability (HRV). Through the sympathetic (SNS) and parasympathetic nervous system (PNS), the autonomic nervous system (ANS) promotes various changes in HRV that reflect the individual's psychophysiological response to stress. FHA patients are characterized by high levels of PNS activation during psychological load, suggesting that parasympathetic hyperactivation could be a pathology marker. In the present study, we examine changes in HRV during observation of erotic, neutral, and disgusting images in 10 patients with FHA [(mean ± S.D.) age: 26.8 ± 5.9] and in 9 controls (age: 25.4 ± 6.4; BMI: 22.47 ± 2.97) to assess the differential activation of PNS and SNS between FHA patients and controls matched for age and without other clinical conditions. Our results showed that FHA patients had significantly higher HRV activation while observing high emotional value images and not during the observation of neutral images confirming a parasympathetic hyperactivation. HRV and cognitive and psychological testing, could provide new insights into understanding such a clinically understudied condition and provide further tools for clinical diagnosis and treatment.